EVALUASI KESEHATAN BANK BERBASIS RISIKO, TATA KELOLA, PROFITABILITAS, DAN PERMODALAN DALAM KERANGKA RGEC PADA PT BANK NEO COMMERCE TBK TAHUN 2022–2024 - Indri Iswardhani (CV. Denasya Smart Publisher, 2026)
This study aims to evaluate the health level of PT Bank Neo Commerce Tbk (BBYB) for the 2022-2024 period using the Risk-Based Bank Rating (RGEC) approach, which includes four main aspects: Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. The research method used is descriptive quantitative analysis with secondary data sourced from BBYB's annual financial reports. The results show that during the 2022-2024 period, BBYB experienced a consistent improvement in its health level, reflected in the composite score increasing from 66.67% (PK-3 with